2003
DOI: 10.1046/j.1460-9568.2003.02747.x
|View full text |Cite
|
Sign up to set email alerts
|

Enabling role of adenosine A1receptors in adenosine A2Areceptor‐mediated striatal expression ofc‐fos

Abstract: When striatal neurons are strongly activated they produce adenosine, which activates nearby adenosine A1 receptors (A1Rs) and adenosine A2A receptors (A2ARs). Although the effects of A1R or A2AR activation on neural activity in the striatum have been examined separately, the effects of coactivating both receptors has not been investigated. Using c-Fos immunohistochemistry as an indicator of neural activity, we examined the effects of coactivation of A1Rs and A2ARs on neural activity and their mechanism of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 53 publications
7
46
0
3
Order By: Relevance
“…In a previous study it was shown that co-administration of the A 1 receptor agonist CPA and the A 2A receptor agonist CGS 21680 increases the expression of the immediate-early gene c-fos in the striatum (Karcz-Kubicha et al, 2003). In the present study, we demonstrate that this increase is selective for the GABAergic enkephalinergic neurons.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In a previous study it was shown that co-administration of the A 1 receptor agonist CPA and the A 2A receptor agonist CGS 21680 increases the expression of the immediate-early gene c-fos in the striatum (Karcz-Kubicha et al, 2003). In the present study, we demonstrate that this increase is selective for the GABAergic enkephalinergic neurons.…”
Section: Discussionsupporting
confidence: 77%
“…However, under normal conditions, the ability of A 2A receptors to activate the cAMP-PKA signaling pathway is restrained by the tonic inhibitory effect of D 2 receptors, which potently inhibit A 2A -receptor mediated adenylyl-cyclase activation (Agnati et al, 2003;Ferré et al, 2003Ferré et al, , 2004. We have shown that activation of adenosine A 1 receptors allows A 2A receptors to overcome the inhibitory effect of D 2 receptors and induce striatal expression of c-fos (Karcz-Kubicha et al, 2003). However, it remained to be demonstrated if this increase in c-fos expression takes place in GABAergic enkephalinergic neurons.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations